A PRISMA-compliant systematic review and meta-analysis of the relationship between thyroid disease and different levels of iodine intake in mainland China. Issue 25 (June 2017) - Weng, Wanwen; Dong, Mengjie; Zhan, Jun; Yang, Jun; Zhang, Bo; Zhao, Xingdong
Abstract: Background: Low-iodine intake has historically been an issue in China, causing widespread iodine deficiency diseases (IDD). China started to introduce universal salt iodization in 1995, but reports of increased thyroid disease are a concern and appropriate levels of iodine intake must be considered. Objective: To assess the prevalence of thyroid disease with different urinary iodine concentrations (UICs) in the general population of those residing in mainland China. Furthermore, we aimed to analyze the relationship between thyroid disease and UIC, to provide guidance in establishing effective health policies regarding iodine intake. Methods: PubMed, Cochrane, Embase, CNKI, Wan fang, and CQVIP databases were searched for random community-based relevant studies with UIC published before January 2016 in mainland China. Two independent reviewers extracted data from eligible citations, and obtained prevalence of thyroid disease for different UICs, as well as the intergroup interaction P values. Results: Forty-three articles were included. The prevalence of thyroid nodules was 22.3% (95% confidence interval [CI]: 20.6%–24.1%) for the low-iodine group, 25.4% (95% CI: 20.8%–28.8%) for the medium-iodine group, and 6.8% (95% CI: 2.8%–11.5%) for the high-iodine group. In the high-iodine group, the prevalence of thyroid nodules was lower than the other groups. The prevalence of 8.3% (95% CI: 3.8%–17.3%) for subclinical hypothyroidism in the high-iodine group was significantly higher than the low- and medium-iodine groups ( P < .01). The prevalence of hypothyroidism in the medium-iodine group was 0.2% (95% CI: 0.1%–0.4%), and was lower than the prevalence of the other 2 groups ( P < .01). There was no difference in prevalence of hyperthyroidism in each group. Conclusions: Thyroid nodules are the most easily detectable thyroid disease. These have a lower prevalence in the high-iodine group. The prevalence of most thyroid diseases is lowest for a UIC ranging from 100 to 299 μg/L. This serves as a reference for health policy-making with respect to iodine levels. Further studies on this topic should be carried out according to sufficient thyroid cancer data. Abstract : Supplemental Digital Content is available in the text